Novel Multifunctional Carbon Nanotube Containing Silver and Iron Oxide Nanoparticles for Antimicrobial Applications in Water Treatment. (2017) - Ali, Qurban; Ahmed, Waqar; Lal, Sham; Sen, Tapas
Abstract: Escherichia coli contamination in drinking water is a significant threat to the human health. In this article, we report a class of novel multifunctional nanocomposites composed of multi-walled carbon nanotubes (MWCNTs) with embedded iron oxide and silver nanoparticles have been reported for antimicrobial efficiency and magnetic separation. The structure, morphology, surface properties, crystallinity, and chemical composition were characterized using Transmission Electron Microscope (TEM), Scanning Electron Microscope (SEM), Nitrogen gas adsorption (BET surface area analysis), Powder X-ray Diffraction (XRD), X-ray Fluorescence (XRF) and Energy Dispersive X-ray Analysis (EDAX). The antibacterial properties of the synthesized composite materials were tested against the E. coli (NCTC 10418) and have shown significant antibacterial activity. The minimum bactericidal concentration (MBC) of the nanocomposite was found to be 200 μg/ml with a minimum bactericidal time for the growth of bacteria at this concentration was found to be 8 hours.